Management of high-quality dehydrated grape in vinification to produce dry red wines. (15th February 2021) - Mencarelli, F.; D'onofrio, C.; Bucci, S.; Baccelloni, S.; Cini, R.; Pica, G.; Bellincontro, A.
Highlights: A new vinification protocol is proposed on Sangiovese and Cesanese grape varieties. Withering process under controlled conditions provides an improvement of grape quality. Basic wines produced through the standard procedure were added of withered grape musts. After 2 nd fermentation, final wines were richer in color, phenols, aroma, body, and structure. Commercial wine quality can be improved by smoother, ready to drink and pleasant aromatic notes. Abstract: Grape controlled dehydration of "Cesanese" and "Sangiovese" wine grapes, followed by an innovative vinification protocol, was studied. Fresh grapes of both varieties were processed into basic wines (IW = initial wine). 'Cesanese' must from pressed dehydrated grapes (solid and liquid) was directly added (15 and 30% v/v) into the IW activating a refermentation. 'Sangiovese' must (solid and liquid) from pressed dehydrated grapes was fermented and, when the wine reached 5% alcohol concentration, every day, the IW was added until a final concentration of 40 or 60% (v/v). The produced "blended wines" (BW) had significantly higher alcohol, glycerol, extract, and polyphenol concentration. Malolactic fermentation was completely ended in all BW with no malic acid and formation of lactic acid (0.5–1 g/L). All wines showed a significant higher concentration in 4-vinylguaiacol, acetovanillone, and 3-oxo-α-ionol, providing spicy and fruity notes at the sensory analyses, and being appreciated for their body balance, less acidity, and flavor intensity.